2011
DOI: 10.1007/s12177-011-9072-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the adrenomedullin/nitric oxide signaling pathway in early diabetic retinopathy

Abstract: The nitric oxide (NO) signaling pathway is integrally involved in visual processing and changes in the NO pathway are measurable in eyes of diabetic patients. The small peptide adrenomedullin (ADM) can activate a signaling pathway to increase the enzyme activity of neuronal nitric oxide synthase (nNOS). ADM levels are elevated in eyes of diabetic patients and therefore, ADM may play a role in the pathology of diabetic retinopathy. The goal of this research was to test the effects of inhibiting the ADM/NO signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…This has subsequently been demonstrated in animal models, in which abundant AM and NO lead to severe acute multiple organ failure (heart, lung, liver and kidney) (25). The link between these two molecules has also been demonstrated clinically in cardiomyopathy and hypertension (27,28), pre-eclampsia (29), intrauterine growth restriction (30), diabetic retinopathy (31), depressive disorders and schizophrenia (32,33). Owing to its regulatory role, AM has been suggested as a marker of disease, for example, in decreased ovarian function (34,35), and as a target for treatment of cancer (36), depression (37) and arrhythmia (38).…”
mentioning
confidence: 94%
“…This has subsequently been demonstrated in animal models, in which abundant AM and NO lead to severe acute multiple organ failure (heart, lung, liver and kidney) (25). The link between these two molecules has also been demonstrated clinically in cardiomyopathy and hypertension (27,28), pre-eclampsia (29), intrauterine growth restriction (30), diabetic retinopathy (31), depressive disorders and schizophrenia (32,33). Owing to its regulatory role, AM has been suggested as a marker of disease, for example, in decreased ovarian function (34,35), and as a target for treatment of cancer (36), depression (37) and arrhythmia (38).…”
mentioning
confidence: 94%
“…Inhibition of adrenomedullin, a peptide involved in vasodilation, angiogenesis and vascular leakage, encoded by Adm gene, highly overexpressed in our study, was identified as a potential target of new therapies in diabetic retinopathy. 18 On the other hand, an increased expression of Gfap gene might indicate reactive gliosis as a reaction to retinal impairment. 19 In previous studies, murine retinal neovascularization as visualized in the tissue samples spontaneously regressed between P17 and P25.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that, early in the pathogenesis of diabetic retinopathy (DR), NO signaling seems to become activated and be associated with retinal dysfunction [82]. Since both DR and ROP are neovascular diseases, we examined whether genes involved in the activation of NOS, the enzyme that generates NO, were regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of NO was recently shown to be effective at preventing neuropathology in the early stages of a mouse model of diabetic retinopathy [82]. The generation of NO is controlled by a family of enzymes, called NO synthase (NOS), which catalyze its production from L-arginine: neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS).…”
Section: Introductionmentioning
confidence: 99%